Cross-border litigation in England and Wales: initial Brexit implications 2016-2018 - Danov, Mihail (UK Data Service, 2019)
The data was gathered through: 1) Self-completion survey questionnaires (which were sent to the Heads of litigation departments and family law firms from there relevant sampling frames drawn from the legal directories). The primary quantitative data (from the self-completion survey) should provide information about the statics of the cross-border litigation pattern (e.g. volume; type of cases). 2) Semi-structured interviews which were conducted with legal practitioners in England and Wales. The primary qualitative data (from the semi-structured Interviews) should provide information about the parties’ strategies (i.e. the dynamics of the cross-border litigation pattern). The purpose of this pilot study was to measure the expected initial impact of Brexit on parties’ strategies which would in turn have a bearing on the litigants’ access to legal remedies (as well as on settlement dynamics) in cross-border disputes. The newly generated data should enable researchers to consider the correlation between a possible change in the legal landscape and the parties’ alternative strategies as well as to analyse the relationship between the litigants’ tactics and private parties’ access to justice in cross-border cases before the English and Welsh courts. On this basis, it would be possible to identify the main issues which would need to be addressed by the UK policy-makers as priority with a view to setting up a well-functioning private international law regime in a post-Brexit context.